Road Traffic Accident Data Visualization: A case study of Bhaktapur - Aryal, Susmita; Dhakal, Swostika (International Journal on Engineering Technology, 2024)
This study focuses on multiple dynamics of road safety. It utilizes a dataset comprising recorded road traffic accidents (RTAs) in Bhaktapur to reveal the patterns, contributing factors, and demographic associations by data visualization. The research uncovers distinct high-risk locations as Thimi, Radhe Radhe, and Sallaghari. Demographic insights and gender-based disparities are observed. The study examines the prevalent modes of transportation involved in RTA. Findings show the addressing of identified issues which can be used for taking actions based on its results.